Acute Renal Infarction Presenting with Acute Abdominal Pain Secondary to Newly Discovered Atrial Fibrillation: A Case Report and Literature Review. (29th December 2014) - Eltawansy, Sherif Ali; Patel, Shil; Rao, Mana; Hassanien, Samaa; Maniar, Mihir
Abstract : We report an 85-year-old female with known history of recurrent diverticulitis presented with abdominal pain. It was believed that the patient again needed to be treated for another diverticulitis and was started on the routine treatment. The initial CT scan of abdomen showed renal infarcts bilaterally that were confirmed by a CT with and without intravenous contrast secondary to unknown cause. An ECG found accidentally that the patient was in atrial fibrillation, which was the attributed factor to the renal infarctions. Subsequently, the patient was started on the appropriate anticoagulation and discharged.